Feasibility and acceptability of a nutritional intervention testing the effects of nitrate-rich beetroot juice and folic acid on blood pressure in Tanzanian adults with elevated blood pressure. (17th February 2021) - Kandhari, Navneet; Prabhakar, Meghna; Shannon, Oliver; Fostier, William; Koehl, Christina; Rogathi, Jane; Temu, Gloria; Stephan, Blossom C. M; Gray, William K.; Haule, Irene; Paddick, Stella-Maria; Mmbaga, Blandina T.; et al.
Abstract: Sub-Saharan African countries are experiencing an alarming increase in hypertension prevalence. This study evaluated the feasibility and acceptability of nitrate-rich beetroot and folate supplementation, alone or combined, for the reduction of blood pressure (BP) in Tanzanian adults with elevated BP. This was a three-arm double-blind, placebo-controlled, parallel randomised clinical trial. Forty-eight participants were randomised to one of three groups to follow a specific 60-day intervention which included a: (1) combined intervention (beetroot juice + folate), (2) single intervention (beetroot juice + placebo), and (3) control group (nitrate-depleted beetroot juice + placebo). Forty-seven participants (age: 50–70 years) completed the study. The acceptability of the interventions was high. Self-reported compliance to the interventions was more than 90% which was confirmed by the significant increase in nitrate and folate concentrations in plasma and saliva samples in the treatment arms. This study provides important information for the design of high-nitrate interventions to reduce BP in Sub-Saharan African countries.